Combination of trabectedin and gemcitabine for advanced soft tissue sarcomas: results of a phase I dose escalating trial of the German Interdisciplinary Sarcoma Group (GISG) - Kasper, Bernd; Sommer, Michaela; Mathew, Monika; Rauch, Geraldine; Hohenberger, Peter (Marine drugs, 2015)
Background: Evaluation of the potential efficacy and safety of combination therapies for advanced soft tissue sarcomas (STS) has increased substantially after approval of trabectedin and pazopanib. Trabectedin's introduction in Europe in 2007 depended mainly on its activity in so-called L-sarcomas (liposarcoma and leiomyosarcoma); combination of trabectedin with other chemotherapies used in STS seems of particular interest. Methods: We initiated within the German Interdisciplinary Sarcoma Group (GISG) a phase I dose escalating trial evaluating the combination of trabectedin and gemcitabine in patients with advanced and/or metastatic L-sarcomas (GISG-02; ClinicalTrials.gov NCT01426633). Patients were treated with increasing doses of trabectedin and gemcitabine. The primary endpoint was to determine the maximum tolerated dose. Results: Five patients were included in the study. Two patients were treated on dose level 1 comprising trabectedin 0.9 mg/m2 on day 1 and gemcitabine 700 mg/m2 on days 1 + 8, every 3 weeks. Due to dose-limiting toxicity (DLT) in both patients (elevated transaminases and thrombocytopenia), an additional three patients were treated on dose level −1 with trabectedin 0.7 mg/m2 plus gemcitabine 700 mg/m2. Of these three patients, two demonstrated another DLT; therefore, the trial was stopped and none of the dose levels could be recommended for phase II testing. Conclusion: The GISG-02 phase I study was stopped with the conclusion that the combination of gemcitabine and trabectedin is generally not recommended for the treatment of patients with advanced and/or metastatic leiomyosarcoma or liposarcoma. Also, this phase I study strongly supports the necessity for careful evaluation of combination therapies.